Penerapan Pendekatan Pembelajaran Culturally Responsive Teaching (CRT) terhadap Hasil Belajar Matematika Peserta Didik Kelas V SD - Saputri, Dea Agni; Sudrajat; Mulyani (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2024)
The learning outcomes of class V students on whole number problems up to 100,000 related to money were initially relatively low. This research aims to improve learning outcomes through a Culturally Responsive Teaching (CRT) approach. The method used is Classroom Action Research (PTK) which consists of two cycles, with each cycle involving one meeting. This research was carried out at SDN Kemakmuran II Cirebon City in the odd semester of the 2024/2025 academic year, involving 31 class V students as research subjects. In cycle I, there were 13 of 31 students who had not reached the KKM or only 41,94% of students who achieved complete learning outcomes. In cycle II there was an increase in learning outcomes, namely there were 27 of 31 students who succeeded in reaching the KKM or percentage of complete learning outcomes of 87,09%. Based on the results of this research, it can be concluded that the CRT approach with the Problem Based Learning (PBL) model assisted by the Kacirebonan Menu Book media which is applied can improve student learning outcomes, especially for whole number problems up to 100,000 related to money.